AKSESIBILITAS YANG DIRASAKAN DAN NIAT MAHASISWA PASCASARJANA UNTUK MENGGUNAKAN SUMBER DAYA ELEKTRONIK PERPUSTAKAAN UNTUK PENELITIAN. - Adefuye, Linus; Grace, Oputa Oby; Elizabeth, Fasina Joke; Aderayo, Adetola (Educational Technology Journal, 2026)
This study examined the perceived accessibility and postgraduate students’ intention to use library e-resources for research. A descriptive survey research design was adopted for the study. A simple random sampling technique was used to select two hundred and forty (240) postgraduates in Tai Solarin Federal University of Education, Ijagun, Ogun state. The instrument for data collection was a self-constructed questionnaire. The data gathered was subjected to descriptive statistics (frequency counts, percentage, and mean), and multiple regression was employed to analyse the data generated at a 0.05 level of significance. Results showed that postgraduate students generally experience a high level of perceived accessibility of the library’s electronic resources. Postgraduate students have a high intention to use library e-resources for research activities; they are strongly motivated and intend to use library e-resources extensively for their research activities. There is a significant relationship between perceived accessibility and postgraduate students’ intention to use library e-resources for research. The study revealed that enhancing accessibility and fostering motivation are key to promoting the effective use of library e-resources among postgraduate students.